2011
DOI: 10.1016/s1413-8670(11)70178-7
|View full text |Cite
|
Sign up to set email alerts
|

Rotavirus infection in a tertiary hospital: laboratory diagnosis and impact of immunization on pediatric hospitalization

Abstract: These results indicate that antigen detection by EIA is a rapid, sensitive and specific method, and could be used in large-scale applications for screening stool samples suspected of RV infection. This study showed decreased incidence of RV infection in hospitalized children prior to the implementation of the national immunization program against RV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 37 publications
1
15
1
1
Order By: Relevance
“…in such cases, RV antigens are routinely investigated and the detection rate of this virus has been approximately 28%. 31 this is a retrospective study aimed to identify the frequency of co-infections of RV and other viruses, like the enteric adenovirus, astrovirus, and norovirus groups, using PCR and Rt-PCR. Furthermore, the clinical and epidemiological characteristics of these patients, and the impact of viral co-infections on their outcome were assessed.…”
Section: Introductionmentioning
confidence: 99%
“…in such cases, RV antigens are routinely investigated and the detection rate of this virus has been approximately 28%. 31 this is a retrospective study aimed to identify the frequency of co-infections of RV and other viruses, like the enteric adenovirus, astrovirus, and norovirus groups, using PCR and Rt-PCR. Furthermore, the clinical and epidemiological characteristics of these patients, and the impact of viral co-infections on their outcome were assessed.…”
Section: Introductionmentioning
confidence: 99%
“…Before the introduction of the group A RV (RVA) vaccine in Brazil, the frequency for this virus in the population with AG in our institution was 30%. The number of RVA positive cases has decreased substantially since then (Pereira et al 2011), while other pathogens are now reported more frequently.…”
mentioning
confidence: 99%
“…Some diagnostic tools for the confirmation of rotavirus infection in children with gastroenteritis have been used routinely in diagnostic laboratories include enzyme linked immunosorbent assay (ELISA), latex agglutination assay (LA), polyacrylamide gel electrophoresis (PAGE), electron microscopy (EM) and real-time reverse transcriptionpolymerase chain reaction (RT-PCR). [23][24][25][26] However, these diagnostic tools are not always applicable in hospitals with limited laboratory facilities. Moreover, some of these diagnostic tools are expensive and time consuming.…”
Section: Discussionmentioning
confidence: 99%